1937
DOI: 10.1139/cjr37b-007
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Sulphur in Wool

Abstract: A modification of Pregl's micromethod for the determination of sulphur in organic compounds has been found to be satisfactory and convenient when applied on a macro scale to wool.The investigation of various methods of cleaning the samples shows that the best results are obtained when the wool wax is extracted with a solvent before washing with water. It is shown that a treatment with dilute hydrochloric acid is not necessary in preparing the sample.Three different procedures have been followed in determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1965
1965
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Saponins are an important class of biosurfactant. Soapnuts have significant levels of saponins and have been used for domestic laundering and cleaning historical textiles for a long time [38], and are also used for cleaning wool in research studies [39,40]. Pliny the Elder wrote that 'It furnishes a juice that is extensively employed in washing wool, and it is quite wonderful how greatly it contributes to the whiteness and softness of wool'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins are an important class of biosurfactant. Soapnuts have significant levels of saponins and have been used for domestic laundering and cleaning historical textiles for a long time [38], and are also used for cleaning wool in research studies [39,40]. Pliny the Elder wrote that 'It furnishes a juice that is extensively employed in washing wool, and it is quite wonderful how greatly it contributes to the whiteness and softness of wool'.…”
Section: Introductionmentioning
confidence: 99%
“…. Soapnuts have significant levels of saponins and have been used for domestic laundering and cleaning historical textiles for a long time , and are also used for cleaning wool in research studies . Saponins are used as medicines and have been investigated in industrial processing and environmental remediation .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Marston (1928) concluded that the sulphur content of wool taken from a variety of fleeces was constant at c. 3·6%, but he stated that it was sometimes necessary to equilibrate the wool in O·OlN HCI to obtain this sulphur content. However, many analyses lower than 3·6% sulphur have been recorded, and Barritt and King (1933) and Larose and Tweedie (1937a) found no change in the sulphur content of several wool samples when treated with HCI. There is now ample evidence (Larose and Tweedie 1937b;Reis and Schinckel 1963) that the sulphur content of wool is variable and the extent of variation is even greater than that originally found by~Barritt and King.…”
Section: Introductionmentioning
confidence: 99%